(untitled) (Canadian Dermatology Today, 2021)
Skin cancer is a leading cause of mortality and morbidity in the post-renal transplant patient. Squamous cell carcinoma (SCC) is the most common post-transplant malignancy (up to 250x more common than in the general population). The three main pathogenetic – and synergistic – risk factors are cumulative ultraviolet light exposure, immunosuppression, and oncogenic viruses, especially human papillomavirus (HPV). How else can the dermatologist impact patient care beyond chasing skin cancers at every visit? This article will focus on a few strategies utilized in the Skin Cancer Post-Renal Transplant Clinic (SCREEN Clinic) at St. Paul’s Hospital in Vancouver, BC.